Outcomes of Crowding in Emergency Departments; a Systematic Review - Rasouli, Hamid Reza; Aliakbar Esfahani, Ali; Nobakht, Mohammad; Eskandari, Mohsen; Mahmoodi, Sardollah; Goodarzi, Hassan; Abbasi Farajzadeh, Mohsen (Archives of Academic Emergency Medicine, 2019)
Introduction: Emergency Department (ED) crowding is a global public health phenomenon affecting access and quality of care. In this study, we seek to conduct a systematic review concerning the challenges and outcomes of ED crowding. Methods: This systematic review utilized original research articles published from 1st January 2007, to 1st January 2019. Relevant articles from the PubMed (MEDLINE), EMBASE, and Google scholar databases were extracted using predesigned keywords. Following the PRISMA guidelines, two reviewers independently evaluated the quality of the studies using Critical Appraisal Skills Programme for cohort studies and qualitative studies, and Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument for studies. Results:Â Out of the total of 73 articles in the final record, we excluded 15 of them because of poor quality. This systematic review synthesized the reports of 58 original articles. The outcomes of multiple individual patients and healthcare-related challenges are comprehensively assessed. Conclusions: ED crowding affects individual patients, healthcare systems and communities at large. The negative influences of crowding on healthcare service delivery result in delayed service delivery, poor quality care, and inefficiency; all negatively affecting the emergency patients’ healthcare outcomes, in turn.